In Reply. (10th August 2017) - Khan, Khurum; Cunningham, David; Aitken, Katharine; Rao, Sheela
Abstract : This Letter to the Editor acknowledges the limitations of a cohort observational study compared with a randomized clinical trial and defends the results of a recent study.